Using Social Determinants Screening/Mapping Tools to Identify Needs and Resources for Student-Run Free Clinic Patients - Akanksha Dadlani; Cooper T. Johnson; Rebecca Fischbein; Stacey L. Gardner-Buckshaw; Amy Lee; John M. Boltri (Ohio Journal of Public Health, 2021)
Background: Social determinants of health have been well accepted as contributing to health outcomes. They are a vital aspect of health care delivery and must be a consideration, especially among free clinic populations. Social determinants of health have also become a required element of medical school curricula. The Student Outreach to Area Residents Student-Run Free Clinic based out of Northeast Ohio Medical University piloted a student-led program that implemented social determinants of health screening and community resource referral as a part of integrated health care delivery for all its patients. Methods: We described the development of a screening tool, protocol, and creation of community resource referral materials. We also described the tracking of patient-reported needs and mapping of location and accessibility of community resources. One hundred patients were surveyed through convenience sampling, and results were used for program improvement. Results/Conclusion: After collecting and analyzing survey results, it was found that the 2 most frequently requested determinants were mental health and utilities services, and the most available community resource was emergency food services. We also mapped these results by zip code and found gaps between need and distribution of services. We demonstrated the utility of mapping to identify points of improvement for the future. We also provided lessons learned related to effective social determinants of health screening, community resource referral, and overall program implementation in student-run free clinics. We further explained the benefits of including similar student-led programs as a way for students to gain practical experience related to social determinants of health.
Keywords: Social determinants of health; Mapping; Student-run free clinic